2007
DOI: 10.1097/01.brs.0000257547.17822.14
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Clarity of the Bryan®, Prodisc-C®, Prestige LP®, and PCM® Cervical Arthroplasty Devices

Abstract: Preoperative and postoperative magnetic resonance imaging scans of 20 patients who had undergone cervical arthroplasty were assessed for imaging quality. Five cases each of the Bryan (Medtronic Sofamor Danek, Memphis, TN), Prodisc-C (Synthes Spine, Paoli, PA), Prestige LP (Medtronic Sofamor Danek), and PCM devices (Cervitech, Rockaway, NJ) were analyzed. Six blinded spinal surgeons scored twice sagittal and axial T2-weighted images using the Jarvik 4-point scale. Statistical analysis was performed comparing qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Although titanium alloy is inferior in strength, it is considered to be suitable for postoperative follow-up using MRI because it produces smaller artifacts due to its lower magnetic susceptibility. As reported for 1.5-T, 14,15 we found that titanium alloy was also advantageous for reducing artifacts, even at 7 T.…”
Section: Discussionsupporting
confidence: 85%
“…Although titanium alloy is inferior in strength, it is considered to be suitable for postoperative follow-up using MRI because it produces smaller artifacts due to its lower magnetic susceptibility. As reported for 1.5-T, 14,15 we found that titanium alloy was also advantageous for reducing artifacts, even at 7 T.…”
Section: Discussionsupporting
confidence: 85%
“…Especially after a symptom-free interval of 2 years recurrent cervical symptoms are often believed to result from vertebrogenic causes. Metal artifacts complicate the evaluation of MRI and CT scans 15,16,17. The absence of neurological deficits demands a nonsurgical treatment leading to a successful outcome in most patients 6.…”
Section: Discussionmentioning
confidence: 99%
“…The clarity of MRI after cervical arthroplasty has been reported. Titanium devices allow for satisfactory imaging of the adjacent and index levels, but non-titanium devices (cobalt-chrome-molybdenum alloys) create significant image distortion, preventing accurate imaging at the index and adjacent levels 2. More recently, it has been demonstrated that magnet strength affects the artifact from cobalt-chrome alloys.…”
Section: Commentarymentioning
confidence: 99%
“…In a study evaluating the ability to visualize the spinal canal and adjacent segments after cervical disc arthroplasty, only the Bryan (Medtronic) and Prestige LP (Medtronic) allowed for adequate visualization. [54] The artifact produced by these implants can be circumvented with the use of non-ferromagnetic biomaterials allowing for postoperative imaging and evaluation in the future. Polymers and ceramics may also be employed in the design of future intervertebral disc prostheses.…”
Section: Motion Preservationmentioning
confidence: 99%